ORGANIZATION OF REPETITION OF THE MATERIAL LEARNED IN MATHEMATICS LESSONS WITH THE HELP OF MULTIMEDIA (American Journal of Pedagogical and Educational Research, 2023)
Until now, people have used repetition in various ways and in very complex ways. People have used such methods for a long time, but after the advent of the Internet, very convenient and fast search methods appeared. In the 21st century, that is, by the age of information technologies, each user has his own profession, and representatives of all fields of the world, artisans, merchants, are widely using it.